THE IMPACT OF CORONA VIRUS ON THE FUTURE OF GLOBAL ECONOMY - Alyaa Suhail Najm (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The effect and impact of the corona virus cannot be over emphasized as it has affected almost every industry worldwide. The world economy is in a state of decline due to the impact and effect the pandemic has on SME. The visible impact is demonstrated in rise in unemployment, decline in the service industry, slump in manufacturing industries, fall in global trade and shrinkage of global economy, among other. The most affected industries worldwide include Aviation, Tourism, Hospitality, Manufacturing, Transportation, Health, Agriculture, Sports. This paper examines the state of global economy before and after the pandemic and focuses on the disaster recovery plan in order for the world global trade and economy to gradually rise and surpass forecast